Inclusion complex of amiodarone hydrochloride with cyclodextrins: preparation, characterization and dissolution rate evaluation - Alexandre Machado Rubim; Jaqueline Bandeira Rubenick; Marcela Maurer; Luciane Varini Laporta; Clarice Madalena Bueno Rolim (Universidade de São Paulo, 2017)
ABSTRACT This study aimed to improve the water solubility of amiodarone hydrochloride (AMH) via inclusion complexes with β-cyclodextrin, methyl-β-cyclodextrin and 2-hydroxypropyl-β-cyclodextrin. Inclusion complexes were developed by physical mixture, coevaporation, spray-drying and freeze-drying. Solid state analysis was performed using X-ray powder diffraction, differential scanning calorimetry and scanning electronic microscopy. Thermodynamic studies demonstrate that the inclusion complexes of drug into different cyclodextrins were an exothermic process that occurred spontaneously. Water solubility and drug dissolution rates were significantly increased after the formation of inclusion complexes with the cyclodextrins evaluated in relation to the physical mixture and pure drug. The present study provides useful information for the potential application of complexation with amiodarone HCl. This may be a good strategy for the development of solid pharmaceutical dosage forms.